Deficiency of Brummer Impaires Lipid Mobilization and JH-Mediated Vitellogenesis in the Brown Planthopper, Nilaparvata lugens - Lu, Kai; Zhou, Jinming; Chen, Xia; Li, Wenru; Li, Yue; Cheng, Yibei; Yan, Jing; You, Keke; Yuan, Zhineng; Zhou, Qiang (Frontiers in Physiology, 2018)
Provisioning of sufficient lipids and vitellogenin to the oocytes is an indispensable process for fecundity of oviparous insects. Acute mobilization of lipid reserves in insects is controlled by the Brummer (Bmm), an orthologous of human adipose triglyceride lipase (ATGL). To investigate the functional roles of brummer-mediated lipolysis in the fecundity of the brown planthopper, Nilaparvata lugens. RNA interference (RNAi) analyses were performed with double-stranded RNA (dsRNA) against NlBmm in adult females. Knockdown of NlBmm expression resulted in obesity and blocked lipid mobilization in the fat body. In addition, NlBmm silencing led to retarded ovarian development with immature eggs and less ovarioles, decreased number of laid eggs, prolonged preoviposition period and egg duration time. Furthermore, severe reductions of vitellogenin and its receptor abundance were observed upon NlBmm knockdown. The transcript levels of NlJHE (juvenile hormone esterase) which degrades JH were up-regulated, whereas the expression levels of JH receptors NlMet (Methoprene-tolerant) and NlTai (Taiman) and their downstream transcription factors NlKr-h1 (Krüppel-homolog 1) and NlBr (Broad-Complex) were down-regulated after suppression of NlBmm. JH-deficient females exhibited impaired vitellogenin expression, whereas JH exposure stimulated vitellogenin biosynthesis. Moreover, JH topical application partially rescued the decrease in vitellogenin expression in the NlBmm-deficient females. These results demonstrate that brummer-mediated lipolytic system is essential for lipid mobilization and energy homeostasis during reproduction in N. lugens. In addition to the classical view of brummer as a direct lipase with lipolysis activity, we propose here that brummer-mediated lipolysis works through JH signaling pathway to activate vitellogenesis and oocyte maturation that in turn regulates female fecundity.